2017
DOI: 10.18632/aging.101114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an unusual poison identify a lifespan role for Topoisomerase 2 in Saccharomyces cerevisiae

Abstract: A progressive loss of genome maintenance has been implicated as both a cause and consequence of aging. Here we present evidence supporting the hypothesis that an age-associated decay in genome maintenance promotes aging in Saccharomyces cerevisiae (yeast) due to an inability to sense or repair DNA damage by topoisomerase 2 (yTop2). We describe the characterization of LS1, identified in a high throughput screen for small molecules that shorten the replicative lifespan of yeast. LS1 accelerates aging without aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…In view of the possibility that the breaks are caused by Top2, it is worth mentioning that in mammalian cells, promoter proximal Top2β, in addition to being implicated in transcriptional regulation ( 39 ), has been incriminated as a crucial player in chromosomal translocations leading to cancer ( 39 , 130–132 ). A further intriguing connection with our findings is represented by recent observations implicating Top2 in the aging of S. cerevisiae ( 109 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In view of the possibility that the breaks are caused by Top2, it is worth mentioning that in mammalian cells, promoter proximal Top2β, in addition to being implicated in transcriptional regulation ( 39 ), has been incriminated as a crucial player in chromosomal translocations leading to cancer ( 39 , 130–132 ). A further intriguing connection with our findings is represented by recent observations implicating Top2 in the aging of S. cerevisiae ( 109 ).…”
Section: Discussionsupporting
confidence: 81%
“…A scenario where the DNA breaks observed herein could be generated by Top2 would be highly attractive: Top2ccs with a single nicked DNA strand (such as those mapped in human colon cancer cells ( 9 )) could tether the bases of loops in concert with topological relaxation with its concomitant nucleosome destabilizing effect ( 67 ). Addressing the possible role of Top2 (or Top3) directly would not be trivial since these enzymes are essential for growth in budding yeast ( 109 , 110 ), have multiple roles in transcriptional regulation ( 15 ), and any break made by Top2 before the transfer of a conditional mutant to restrictive conditions is expected to persist even after the enzymes are down-regulated, inhibited, subjected to heat-reversal, or upon inactivation ( 111–114 ). The findings that in the bulk of gDNA Top2 contributes to the assembly of the RNAP II preinitiation complex ( 102 , 103 ), whereas the depletion of Top2 appears to unslilence RNAP II related ncRNA transcription in rDNA ( 77 ), fit the correlation between nick incidence and RNAP II promoter activity in gDNA on the one hand, and between nicking in rDNA and rDNA silencing on the other.…”
Section: Discussionmentioning
confidence: 99%
“…Genome instability increases with aging, at least in part, due to decreased capacity to repair DNA damage. DNA double strand break (DSB) repair appears to be particularly compromised as a function of replicative age in both yeast and mammals as they approach senescence in culture . Moreover, there is significant data to indicate that DSB repair decreases during aging in mice and humans as indicated by increased numbers of phosphorylated H2A.X (γ‐H2Ax) foci that appear in aged tissues .…”
Section: Proteomics and The Hallmarks Of Agingmentioning
confidence: 99%
“…Similarly, S1495 and S1449 of topoisomerase (TOP2A) are only present in the long‐lived species. Although modification of this residue has not yet been studied, yeast TOP2 hypomorphs extend replicative lifespan and several mutations or truncations in the C‐terminal domain of human TOP2 behave as hypomorphs that confer resistance to cancer drugs such as doxorubicin . The C‐terminal domain is not part of the conserved core and is thought to modulate protein interactions as well as overall activity.…”
Section: Longevity‐specific Ptm Sites?mentioning
confidence: 99%
“…In YMM10 strain, genes encoding nine different types of transmembrane drug-efflux pump proteins are deleted. A study has reported that YMM10 strain displays improved drug accumulation and enhanced sensitivity to ETP (Tombline et al, 2017). For immunodetection of yeast TOP1, N-terminally HA-tagged TOP1 cDNA was amplified by PCR using primers and inserted in NcoI/XhoI sites of pYX112 vector.…”
Section: Yeast Strains and Plasmidsmentioning
confidence: 99%